Analisis Kadar Lemak dan Kadar Air pada Simplisia Biji Kakao (Theobrama Cacao L.) Desa Gumbrih, Kecamatan Pakutatan, Kabupaten Jembrana - Sugiantari, Widiya; Chandra Wibawa, Agung Ari; Pramitha, Dewa Ayu Ika (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2023)
Cocoa fruit seeds derived from the cocoa plant (Theobroma cacao L.) is one of the raw materials that are very widely used in the community either as food, beverages, or additives in the pharmaceutical field. The content of primary metabolite compounds in cocoa beans such as fat, carbohydrates, water and protein is a very important standard in determining the quality of cocoa beans. Fat and water content is the first parameter in determining the quality and quality of cocoa beans. Gumbrih Village, Jembrane sub-district, Bali is currently one of the largest suppliers of cocoa beans in Bali for export. However, there is no data related to fat and water content. This study was conducted with the aim of knowing the quality standards of fat content and water content in cocoa beans from Gumbrih Village, Pakutatan District, Jembrana Regency, as well as to determine the relationship between the effect of water content on fat content. The research design uses experimental research in the laboratory with the aim of analysis. Method used in this study is the analysis of fat content using the soxlhetation method with N-hexane solvent and in the analysis of water content using the gravimetric method. The results showed that the cocoa bean samples in Gumbrih Village, Pakutatan District, Jembrana Regency did not meet the quality standards with an average fat content of (55.95±1.64)% and an average water content that did not meet the quality requirements of (9.5±0.47)%.